1992
DOI: 10.1037/h0079362
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent suicide attempts: Outcomes at follow-up.

Abstract: Adolescents seen in a general hospital emergency department or psychiatrically hospitalized were followed up at one month and three months following a suicide attempt. Findings included substantial drop-out rates for psychotherapy and high rates of repeated suicide attempts by three months. Implications for disposition planning and care of such adolescents are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 11 publications
1
73
0
2
Order By: Relevance
“…Youths who attempt or contemplate suicide would be expected to have high levels of psychological distress following their suicidality. Empirical data on heterosexual youths support this hypothesis (e.g., Laurent et al, 1998;Lewinsohn et al, 1994;Pfeffer et al, 1993;Spirito et al, 1992). For example, in a large cohort of adolescents (Fergusson & Lynskey, 1995), youths who reported a past suicide attempt (at or prior to age 14) were 17 times more likely to be diagnosed (at age 16) with a mood disorder, 5 times more likely to be diagnosed with an anxiety disorder, and 13 times more likely to be diagnosed with conduct disorder.…”
mentioning
confidence: 55%
“…Youths who attempt or contemplate suicide would be expected to have high levels of psychological distress following their suicidality. Empirical data on heterosexual youths support this hypothesis (e.g., Laurent et al, 1998;Lewinsohn et al, 1994;Pfeffer et al, 1993;Spirito et al, 1992). For example, in a large cohort of adolescents (Fergusson & Lynskey, 1995), youths who reported a past suicide attempt (at or prior to age 14) were 17 times more likely to be diagnosed (at age 16) with a mood disorder, 5 times more likely to be diagnosed with an anxiety disorder, and 13 times more likely to be diagnosed with conduct disorder.…”
mentioning
confidence: 55%
“…One treatment strategy, Dialectical Behaviour Therapy, has been found to significantly reduce the number of suicidal acts within one year in 18 -45 years old females with previous parasuicide incidents [38]. Since repetition often occurs soon after the attempt, i.e., within 4 weeks [11] or 12 weeks [37,39,40,41], risky behaviour such as early repetition ought to be considered. At a suicide attempt special attention should be put to those with several previous attempts to prevent further repetitive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Spirito et al (1992) found that 16.7% of adolescents presenting to a general hospital after a suicide attempt used alcohol at least once a week at a three-month follow-up Additionally, hospitalized adolescent suicide attempters have been shown to be more likely to drink at least weekly or meet criteria for alcohol abuse than non-suicidal pediatric controls between 5 and 15 years later (Laurent, Foussard, David, Boucharlat, & Bost, 1998;Otto, 1972). None of these studies reported assessing drinking patterns prior to the attempt, limiting our ability to determine whether post-attempt drinking was a consequence of the suicide attempt.…”
Section: Distal Effects Of S→amentioning
confidence: 99%
“…School changes may be voluntary, due to moving or embarrassment/ harassment because of the attempt, or involuntary (e.g., expelled or denied enrollment). One study documented that 23% of adolescent suicide attempters were subsequently involved in physical fighting three months post-hospitalization (Spirito et al, 1992). In addition, young adults who attempt suicide often are not allowed to continue college enrollment due to fears of litigation (Bender, 2006;Moran, 2006) which disrupts a student's social world.…”
mentioning
confidence: 99%